VEP examination with new portable device - Kuba, Miroslav; Kremláček, Jan; Vít, František; Kubová, Zuzana; Langrová, Jana; Szanyi, Jana; Chutná, Marie (Documenta ophthalmologica. Advances in ophthalmology, 2023)
INTRODUCTION: We developed a new portable device called "VEPpeak" for the examination of visual evoked potentials (VEPs) to extend VEP examination beyond specialized electrophysiological laboratories and to simplify the use of this objective, noninvasive, and low-cost method for diagnostics of visual and central nervous system dysfunctions. METHODS: VEPpeak consists of a plastic headset with a total weight of 390 g containing four EEG amplifiers, an A/D converter, a control unit, and a visual LED stimulator built in the front, vertically adjustable peak. The device is powered and controlled via USB connection from a standard PC/notebook using custom software for visual stimuli generation and for VEP recording and processing. Up to four electrodes can be placed at any scalp location or in combination with two dry electrodes incorporated into the headset. External visual stimulators, such as a tablet, can be used with synchronization. Feasibility and validation studies were conducted with 86 healthy subjects and 76 neuro-ophthalmological patients including 67 who were during the same session also tested with a conventional VEP system. RESULTS: VEPpeak recordings to standard (pattern-reversal) and non-standard (motion-onset, red-green alternation) were robust and repeatable and obtained also in immobilized patients. Good comparability of results was achieved between VEPpeak and standard examination. Some systematic differences in peak latencies and amplitudes are consistent with differences in stimulus characteristics of the two compared systems. DISCUSSION: VEPpeak provides an inexpensive system for clinical use requiring portability. In addition to ISCEV standard VEP protocols, free choice of stimuli and bio-signal recordings make the device universal for many electrophysiological purposes.
Keywords: Evoked Potentials, Visual; Motion-onset; Visual Cortex; Cognitive ERP; elektrody; zrakové evokované potenciály; VEPpeak; elektroretinografie; lidé; Electrodes; zrakové korové centrum; Photic Stimulation; VEP diagnostics; VEP portable device; Electroretinography; Humans; světelná stimulace; Pattern-reversal